Epitaxial growth of Si/SiC heterostructures with different preferred orientations on 6H-SiC(0001) by LPCVD. Issue 30 (24th June 2016) - Li, L. B.; Chen, Z. M.; Zang, Y.; Song, L. X.; Han, Y. L.; Chu, Q.
Abstract : The in-plane orientations of Si/SiC heterojunctions on 6H-SiC(0001) were investigated by high-resolution X-ray diffraction. Abstract : The in-plane orientations of Si/SiC heterojunctions on 6H-SiC(0001) were investigated by high-resolution X-ray diffraction. An Si(111)/SiC(0001) heterostructure with an in-plane orientation of Si[01−1]//SiC[110] is achieved at 900 °C, the Si/6H-SiC interface has a 4 : 5 Si-to-SiC matching mode with a residual lattice mismatch of 0.26%, and the edge dislocation density at the Si/SiC interface is calculated to be 4.87 × 10 13 cm −2 . As the growth temperature is increased to 1050 °C, the [110] preferential growth with an in-plane orientation of Si[−110]//SiC[0−10] is observed, along Si[001]SiC[210] orientations, the Si-to-SiC mode changes to approximately 1 : 2 and the residual mismatch is 1.84%. The edge dislocation density increases to 1.22 × 10 14 cm −2 correspondingly.